'Hell has no flames, only windows that won't open': justice as escape in law and literature. Issue 2 (3rd July 2019) - Gurnham, David
ABSTRACT: Struggles for justice are commonly articulated in literature and drama through metaphors of physical encumbrance (of being cramped, constrained, entangled and mired) and escape (to open landscapes and a view of the horizon and sky). What is less well known or observed is that this metaphorical opposition of encumbrance/escape plays an important role in legal language too. This article traces the appearance of this metaphor across some key moments in English criminal law in which in justice is conceptualized metaphorically in terms of being held up, kept down or back, etc. and that achieving a just outcome necessitates shaking off the encumbrance and getting free. Through a close reading of some important legal judgments, it shows how establishing this intersection between law and literature helps to advance our understanding of the plausibility and persuasiveness of legal language. The article applies this insight to producing a new reading of the Supreme Court's recent reworking of dishonesty in Ivey v Genting Casinos [2017] SC 67, as well as a novel re-examination of established and apparently familiar authorities on recklessness and excuses to murder.